2017
DOI: 10.3727/096368917x695326
|View full text |Cite
|
Sign up to set email alerts
|

Recipient Adipose-derived Stem Cells Enhance Recipient Cell Engraftment and Prolong Allotransplant Survival in a Miniature Swine Hind-limb Model

Abstract: Donor mesenchymal stem cells (MSCs) could prolong vascularized composite allotransplantation (VCA) survival in our previous studies. However, recipient adipose tissue is easier to harvest than donor tissue for preconditioning modulation. Hence, this study investigated the efficacy of recipient autologous adipose-derived stem cells (rADSCs) for VCA survival. The heterotopic hind-limb transplantation from female donor to male recipient was performed in outbred miniature swine. Group I (n ¼ 6) was untreated contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Adipose-derived stem cells are harvested from the recipient and require no pre-conditioning, therefore making their use less taxing to the recipient 64 . In adipose-derived stem cell studies, Kou et al 64 found that outbred swine treated with adiposederived stem cells, tacrolimus, and irradiation (n = 8) had significantly increased graft survival over 196 days. They also found an increase in regulatory T-cells in this group at 6 weeks posttransplant, but these levels normalized by week 15.…”
Section: Large Animal Protocolsmentioning
confidence: 99%
“…Adipose-derived stem cells are harvested from the recipient and require no pre-conditioning, therefore making their use less taxing to the recipient 64 . In adipose-derived stem cell studies, Kou et al 64 found that outbred swine treated with adiposederived stem cells, tacrolimus, and irradiation (n = 8) had significantly increased graft survival over 196 days. They also found an increase in regulatory T-cells in this group at 6 weeks posttransplant, but these levels normalized by week 15.…”
Section: Large Animal Protocolsmentioning
confidence: 99%
“…For CNIs, MSCs combined with tacrolimus demonstrated considerable coordination in immune regulation after organ transplantation. Kuo et al found that MSCs plus tacrolimus improved graft survival in a miniature swine hind-limb model 124 . Suda and his group also showed that the combination of MSCs and tacrolimus could relieve ischemic brain damage in rats 125 .…”
Section: Mscs Combined With Immunosuppressive Drugs In Liver Transplamentioning
confidence: 99%
“…Several papers have briefly discussed porcine fat isolation and characterization but only as part of an in vivo experiment or in experiments without survival surgeries. Many of these studies have used culture conditions identical to those used for humans [3][4][5][6][7][8][9][10][11][12][13]. Here, we provide specific surgical techniques for porcine fat harvest as a survival surgery and describe pADMSC isolation and culture optimization for autologous transplantation, including culture conditions that produce porcine MSCs that are analogous to those cultured from humans, with similar proliferation and differentiation capacities.…”
Section: Introductionmentioning
confidence: 99%